PERSEPSI PARTISIPASI AKTIF SISWA DENGAN HASIL BELAJAR MATEMATIKA DALAM IMPLEMENTASI KURIKULUM MERDEKA - Widiyanto, Priza; Afghohani, Afif (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2025)
This research was conducted to determine the relationship between the perception of active participation of students at SMP Negeri 1 Sambi and their mathematics learning outcomes. Data from this quantitative research obtained from tests and questionnaires will be processed using correlation tests and linear regression. The population in the study was class VIII of SMP Negeri 1 Sambi, which was 259 students. Using a random method, each class was considered a cluster. The sample in this study was students at SMP Negeri 1 Sambi and was considered as one cluster, totalling 114 students. The analysis used simple linear regression SPSS from the t-test on the data that had been obtained about the relationship between the perception of active participation of students and their mathematics learning outcomes. The results of this study indicate that the active participation of students has a positive effect on mathematics learning outcomes, which means that the higher the active participation in learning, the higher the learning outcomes, with the regression equation being Y = 63.717 + 0.286X.